Financial-related discrimination and socioeconomic inequalities in psychological well-being related measures: a longitudinal study - Lucy Bridson; Eric Robinson; I Gusti Ngurah Edi Putra (BMC, 2024)
Abstract Background This study examined the prospective association between financial-related discrimination and psychological well-being related measures and assessed the role of financial-related discrimination in explaining socioeconomic inequalities in psychological well-being related measures. Methods Data of UK older adults (≥ 50 years) from the English Longitudinal Study of Ageing were used (baseline: Wave 5, 2010/2011; n = 8,988). The baseline total non-pension wealth (in tertiles: poorest, middle, richest) was used as a socioeconomic status (SES) measure. Financial-related discrimination at baseline was defined as participants who reported they had been discriminated against due to their financial status. Five psychological well-being related measures (depressive symptoms, enjoyment of life, eudemonic well-being, life satisfaction and loneliness) were examined prospectively across different follow-up periods (Waves 6, 2012/2013, 2-year follow-up; and 7, 2014/2015, 4-year follow-up). Regression models assessed associations between wealth, financial-related discrimination, and follow-up psychological measures, controlling for sociodemographic covariates and baseline psychological measures (for longitudinal associations). Mediation analysis informed how much (%) the association between wealth and psychological well-being related measures was explained by financial-related discrimination. Results Participants from the poorest, but not middle, (vs. richest) wealth groups were more likely to experience financial-related discrimination (OR = 1.97; 95%CI = 1.49, 2.59). The poorest (vs. richest) wealth was also longitudinally associated with increased depressive symptoms and decreased enjoyment of life, eudemonic well-being and life satisfaction in both 2-year and 4-year follow-ups, and increased loneliness at 4-year follow-up. Experiencing financial-related discrimination was longitudinally associated with greater depressive symptoms and loneliness, and lower enjoyment of life across follow-up periods. Findings from mediation analysis indicated that financial-related discrimination explained 3-8% of the longitudinal associations between wealth (poorest vs. richest) and psychological well-being related measures. Conclusions Financial-related discrimination is associated with worse psychological well-being and explains a small proportion of socioeconomic inequalities in psychological well-being.